An approach to greener overseas transport chain planning in FVL - Beškovnik, Bojan (Array, 2021)
The article deals with a very topical issue of environmental suitability of complex transport chains. Overseas transport chains in finished vehicle logistics (FVL) consist of a series of transport routes in which they successively combine rail, road and sea transport. It is necessary to know the input parameters and their impact on the operation of FVL, especially with the aim of evaluating the air pollutants produced and the energy efficiency (EE) achieved. The article gives a systematic approach in defining input parameters and their evaluation for efficient green transport chain planning. The applicability of the approach is demonstrated on an ongoing FVL of the export flow of luxury vehicles from Europe to Asian markets. Transport chains from four production sites in Central Europe to two loading ports in Koper and Bremerhaven, and in maritime RO-RO transport to four Asian unloading ports are analyzed. The results of the study show the need for more comprehensive planning of export FVL, including environmental assessment at the planning stage. Significant savings in energy consumption and reduction in GHG (greenhouse gas) emissions can be achieved by shifting cargo flows to the southern transportation route. The article enriches the current research on sustainable operation of FVL and provides applied results for infrastructural adaptation of the southern transport route.